Unwanted Sexual Acts Among University Students: Correlates of Victimization and Perpetration - Campbell, Jacquelyn C. (Journal of interpersonal violence, 2021)
Unwanted sexual experiences are common among university students in the United States and pose a substantial public health concern. Campus policies and programs to prevent unwanted sexual incidents in university settings require research on prevalence and risk correlates of both victimization and perpetration. This study determined the prevalence of unwanted sexual victimization and perpetration experiences among students, both before and after joining the university, and examined risk correlates for both unwanted sexual victimization and perpetration experiences. Data were collected from 3,977 full-time graduate and undergraduate students using an online survey in a large private university. The findings revealed nearly one in eight students surveyed were victimized by unwanted sexual incidents at the university. Risk correlates of victimization by unwanted sexual incidents included female gender, undergraduate student status, and victimization experiences prior to joining the university. Most (95.5%) sexual violence incidents occurred when the victim was incapacitated due to alcohol, substance, or asleep. An acquaintance, peer, or colleague was the most frequently reported perpetrator. Risk correlates of perpetration included male gender, undergraduate student status, and perpetration of unwanted sexual activities before joining the university. Perpetrators most frequently reported perpetration of unwanted sexual behaviors against a current or former intimate partner or a stranger. The findings highlight the importance of enhanced efforts to reduce prevalence of unwanted sexual incidents, particularly among students most at risk for victimization and perpetration.